The effectiveness of a weight loss diet in a group of overweight and obese women with recurrent depressive disorders - Stefańska, Ewa; Wendołowicz, Agnieszka; Konarzewska, Beata; Ostrowska, Lucyna (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: The research conducted among patients with depression shows that such patients commit a range of nutritional mistakes which may predispose them to the development of many diseases including obesity and its complications. Aim of the study was to assess the effectiveness of a balanced weight loss diet in a group of women with recurrent depressive disorders. Material and methods : 60 women suffering from depression, aged 41-64 (mean 52 ±5.3) on a six-month weight loss diet took part in the study. The patients’ nutrition was assessed both in terms of quality and quantity, they were also subjected to anthropometric tests and their body composition was analysed. Results: An average reduction in the women’s body weight was 4.1 ±3.1 kg. The percentage content of the fatty tissue was reduced by 2.5 ±1.1% on average after modification of the nutrition (a statistically significant decrease in the frequency of wheat bread, cream, fat pork and eggs was observed). A considerable reduction in the mean energy value of the diet and a decrease in the total fat supply was also implemented. Conclusions : It seems that the dietary procedure which is aimed at obtaining the most advantageous effects of the reduction in the body mass of obese patients suffering from depression should be based not only on proper selection of food products and reduction in the energy value of the diet, but it should also take into account actions aimed at introducing permanent lifestyle changes including increased motivation of the patients to undertake physical activity.